(untitled) (Research, Society and Development, 2022)
Toxic epidermal necrolysis (TEN) is a mucocutaneous disorder characterized by the detachment of epidermal and mucous tissues and areas of necrosis, resulting from hypersensitivity reactions to different drugs. We report a clinical case of a 19-year-old male patient diagnosed with TEN, with 90% involvement of the body surface and severe oral involvement. The patient was monitored by dentists from the multidisciplinary team of an intensive care unit, where adjuvant treatment was performed through photobiomodulation to control pain and regenerate the oral mucosa. The case represents the importance of early performance in oral TEN injuries and the role of the multidisciplinary team for comprehensive treatment.